Platelet to Lymphocyte Percentage Ratio Is Associated With Brachial–Ankle Pulse Wave Velocity in Hemodialysis - Chen, Szu-Chia (Medicine (Baltimore), 2016)
Increased arterial stiffness in patients receiving hemodialysis (HD) is highly prevalent and is associated with cardiovascular morbidity and mortality. In HD, inflammation is one of the major causes of increased arterial stiffness. Activation of platelets and decreased lymphocyte percentage (LYMPH%) may exhibit inflammation. The aim of this study is to examine the relationship between platelet to LYMPH% ratio and arterial stiffness in HD patients. A total of 220 patients receiving HD were enrolled in this study. The brachial–ankle pulse wave velocity (baPWV) was measured using an ankle–brachial index form device. Multivariate linear regression analysis was performed to investigate the relations of the platelet to LYMPH% ratio and baPWV. The value of the platelet to LYMPH% ratio was 59.2 ± 33.3 (10(9) cells/L/%). After multivariate stepwise analysis, diabetes (β: 163.973, P = 0.02), high systolic blood pressure (per 1 mm Hg, β: 9.010, P < 0.001), high platelet to LYMPH% ratio (per 10(9) cells/L/%, β: 3.334, P < 0.01), and low albumin (per 0.1 mg/dL, β: −55.912, P < 0.001) were independently associated with an increased baPWV. Furthermore, high white blood cells (per 10(9) cells/L, β: 3.941, P < 0.001), high neutrophil percentage (per 1%, β: 1.144, P < 0.001), and high CRP (per 1 mg/L, β: 9.161, P = 0.03) were independently associated with an increased platelet to LYMPH% ratio. An increased platelet to LYMPH% ratio is associated with an increased baPWV in HD patients. An easy and inexpensive laboratory measure of platelet to LYMPH% ratio may provide an important information regarding arterial stiffness in patients with HD.